2019
DOI: 10.7759/cureus.4423
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between rs3212986C>A Polymorphism and Tumor Stage in Lung Cancer Patients

Abstract: Background The nucleotide excision repair (NER) system is one of the most important deoxyribonucleic acid (DNA) repair mechanisms and is critical for chemotherapy resistance. We conducted the present study to investigate the association between two polymorphisms of excision of repair cross-complementing group 1 (ERCC1), the key component of the NER pathway, and the clinicopathological features of patients with non-small cell lung cancer (NSCLC). Methods A total of 38 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Research on the ERCC1/2 gene polymorphisms in non-small cell lung cancer (NSCLC) has mainly focused on disease susceptibility and the efficacy and prognosis of platinum-based chemotherapy (3)(4)(5)(6)(7). Numerous studies have shown that the low expression of ERCC1 protein in tumor tissue can improve the sensitivity and survival of platinum-based chemotherapy patients.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the ERCC1/2 gene polymorphisms in non-small cell lung cancer (NSCLC) has mainly focused on disease susceptibility and the efficacy and prognosis of platinum-based chemotherapy (3)(4)(5)(6)(7). Numerous studies have shown that the low expression of ERCC1 protein in tumor tissue can improve the sensitivity and survival of platinum-based chemotherapy patients.…”
Section: Introductionmentioning
confidence: 99%
“…We then looked for those findings in other datasets including the GSE84339 from the GEO and also the TCGA data. We identified that in the GSE40419 data, the Red module contains CYP2A6, CYP4Z2P, FAM196B, FAM192A, KCNT1 and MLLT11 genes and the Turquoise module contains C7orf57, CAPSL, CCDC78, CD300LG, CYP2F1, DLEC1, DNAH6, FAM92B, LEFTY2, PI16, PPMIE, PZP, ROPN1L, RSPH1, SCGB1A1, SCGB3A1, SPAG6, TACR2 genes previously reported in association with the lung cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Other polymorphisms are also significantly associated with the risk of lung cancer; for example those in XRCC1 and TP53, especially in individuals aged over 50 years, whose detection allows the earlier diagnosis of disease [9]. ERCC1 and XRCC1 polymorphisms have also been significantly associated with the risk of lung cancer, especially in non-smokers [2][3][4][5]. Additionally, Chaszczewska et al reported that a nuclear factor kappa B subunit 2 polymorphism may be associated with NSCLC risk in the Polish population, and is a potential marker for NSCLC in men [10].…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is one of the common malignant tumors in the world, and it remains the leading cause of cancer mortality because of its high malignant and metastatic potential [1]. Epidemiological studies of migrant populations point to a role for environmental and/or lifestyle factors in cancer etiology [2][3][4][5][6]. The occurrence of lung cancer is closely related to smoking, as shown by its observed downward trend in global incidence with the launch of anti-smoking campaigns; however, it still ranks first among all cancer types.…”
Section: Introductionmentioning
confidence: 99%